Further delineation of Temtamy syndrome of corpus callosum and ocular abnormalities. Issue 3 (31st January 2018) - Alrakaf, Laila; Al‐Owain, Mohammed A.; Busehail, Maryam; Alotaibi, Maha A.; Monies, Dorota; Aldhalaan, Hesham M.; Alhashem, Amal; Al‐Hassnan, Zuhair N.; Rahbeeni, Zuhair A.; Murshedi, Fathiya Al; Ani, Nadia Al; Al‐Maawali, Almundher; et al.
Abstract : Temtamy syndrome is a syndromic form of intellectual disability characterized by ocular involvement, epilepsy and dysgenesis of the corpus callosum. After we initially mapped the disease to C12orf57, we noted a high carrier frequency of an ancient startloss founder mutation [c.1A>G; p.M1?] in our population, and variable phenotypic expressivity in newly identified cases. This study aims to combine 33 previously published patients with 23 who are described here for the first time to further delineate the phenotype of this syndrome. In addition to the known p.M1? founder, we describe four novel homozygous variants, thus increasing the number of Temtamy syndrome‐related C12orf57 variants to seven, all but one predicted to be loss of function. While all patients presented with intellectual disability/developmental delay, the frequency of other phenotypic features was variable: 73.2% (41/56) had epilepsy, 63% (34/54) had corpus callosal abnormalities, 14.5% (8/55) had coloboma, and 16.4% (9/55) had microphthalmia. Our analysis also revealed a high frequency of less recognized features such as congenital heart disease (51.4%), and brain white matter abnormalities (38%, 19/50). We conclude that C12orf57 variants should be considered in the etiology of developmental delay/intellectual disability, even when typical syndromic features are lacking, especially in those who trace their ancestry to Saudi Arabia where a founder C12orf57 mutation is among the most common recessive causes of intellectual disability.